Living standards and income dynamics - T. I. Gordievich; P. V. Ruzanov (Омский научный вестник: Серия "Общество. История. Современность")
Problem and purpose. The main problem of the modern Russian economy has been the declining dynamics of population incomes. Revenues determine the socioeconomic orientation of the economy and are indicators of the standard of living of the population. These are key indicators of social welfare, which are a source of meeting diverse needs. The aim of the article is to study the main trends in the indicators of living standards. Methods. The research methodology is based on the analytical method. In particular, the incomes of the population are examined and the state of living standards of the population is estimated. Results. In the course of the analysis, the dynamics of the average per capita cash income of the population (per month), the real disposable cash income of the population, the volume and structure of the cash income of the population by source of income, the distribution of income, the dynamics of the living wage, and real wages are determined. The analysis carried out in the article allows us to determine the degree of change in the standard of living of the population. In 2014–2015, there was a decrease in the standard of living of the population. In 2016-2017, the economy is growing slowly. Conclusions. A stimulating income policy is needed to improve living standards. In particular, it is necessary to expand the expenditures of the state budget to support poor citizens. Also, an increase in the living standard may become an instrument of income policy